Inicjatywa wspólnotowa URBAN jako narzędzie polityki Unii Europejskiej w zakresie rozwoju obszarów miejskich - Piekarski, Maciej (Community Initiative URBAN as a Tool of the EU Policy Concerning URBAN Areas Development, 2006)
Europe is a continent characterised by high degree of urbanization. Nowadays about half of the population live in cities and towns with more than 50 000 inhabitants. The URBAN areas are, on the one hand, centres of economy, culture, science and technology but on the other they face major problems such as multiple deprivation, economic and social exclusion, degradation of both the natural and built environment, congestion, crime, intolerance and racism, and loss of a sense of community. That leads us to idea of sustainable URBAN development. The purpose of this paper is to present EU URBAN development policy. In particular there is described an instrument of the policy - Common Initiative URBAN, its history, goals, actions and achievements.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 438-449